Costs and quality of life associated with acute upper gastrointestinal bleeding in the UK: cohort analysis of patients in a cluster randomised trial. Issue 4 (29th April 2015) - Campbell, H E; Stokes, E A; Bargo, D; Logan, R F; Mora, A; Hodge, R; Gray, A; James, M W; Stanley, A J; Everett, S M; Bailey, A A; Dallal, H; et al.
Abstract : Objectives: Data on costs associated with acute upper gastrointestinal bleeding (AUGIB) are scarce. We provide estimates of UK healthcare costs, indirect costs and health-related quality of life (HRQoL) for patients presenting to hospital with AUGIB. Setting: Six UK university hospitals with >20 AUGIB admissions per month, >400 adult beds, 24 h endoscopy, and on-site access to intensive care and surgery. Participants: 936 patients aged ≥18 years, admitted with AUGIB, and enrolled between August 2012 and March 2013 in the TRIGGER trial of AUGIB comparing restrictive versus liberal red blood cell (RBC) transfusion thresholds. Primary and secondary outcome measures: Healthcare resource use during hospitalisation and postdischarge up to 28 days, unpaid informal care, time away from paid employment and HRQoL using the EuroQol EQ-5D at 28 days were measured prospectively. National unit costs were used to value resource use. Initial in-hospital treatment costs were upscaled to a UK level. Results: Mean initial in-hospital costs were £2458 (SE=£216) per patient. Inpatient bed days, endoscopy and RBC transfusions were key cost drivers. Postdischarge healthcare costs were £391 (£44) per patient. One-third of patients received unpaid informal care and the quarter in paid employment required time away from work. Mean HRQoL for survivors was 0.74. Annual initial inhospital treatment cost for all AUGIB cases in the UK was estimated to be £155.5 million, with exploratory analyses of the incremental costs of treating hospitalised patients developing AUGIB generating figures of between £143 million and £168 million. Conclusions: AUGIB is a large burden for UK hospitals with inpatient stay, endoscopy and RBC transfusions as the main cost drivers. It is anticipated that this work will enable quantification of the impact of cost reduction strategies in AUGIB and will inform economic analyses of novel or existing interventions for AUGIB. Trial registration number: ISRCTN85757829 and NCT02105532 .